2018
DOI: 10.5125/jkaoms.2018.44.4.167
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical position of the mandibular canal in relation to the buccal cortical bone: relevance to sagittal split osteotomy

Abstract: ObjectivesClassification of the degree of postoperative nerve damage according to contact with the mandibular canal and buccal cortical bone has been studied, but there is a lack of research on the difference in postoperative courses according to contact with buccal cortical bone. In this study, we divided patients into groups according to contact between the mandibular canal and the buccal cortical bone, and we compared the position of the mandibular canal in the second and first molar areas.Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the contrast is lower than that of CT, which makes detecting anatomical structures 25 automatically, comparatively harder. 2) Since the mandibular canal travels in various directions in three dimensions 26,27 , it is difficult to know the exact shape of the canal in a single direction. The challenging part is the change in the location and shape of the mandibular canal in cross-section images due to changes in the head position.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the contrast is lower than that of CT, which makes detecting anatomical structures 25 automatically, comparatively harder. 2) Since the mandibular canal travels in various directions in three dimensions 26,27 , it is difficult to know the exact shape of the canal in a single direction. The challenging part is the change in the location and shape of the mandibular canal in cross-section images due to changes in the head position.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the IAN traverses the mandible through the mandibular foramen, the inferior alveolar canal, and exits through the mental foramen to provide sensory innervation to the lower lip and chin. This canal, on average, resides 4.9 mm from the buccal cortical margin and 17.4 mm from the alveolar crest 35. Intra-operatively, the left IAN was not found within the distal segment.…”
Section: Discussionmentioning
confidence: 87%
“…This canal, on average, resides 4.9 mm from the buccal cortical margin and 17.4 mm from the alveolar crest. 35 Intra-operatively, the left IAN was not found within the distal segment. Instead, the nerve was noted to exit the mandible through the lateral cortex of the ascending ramus posterior to the external oblique ridge (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Lee et al [28] evaluated 58 facial CT scans and found the mean value of the horizontal length between the inferior alveolar canal and the buccal cortical bone as 5.9-6.8 mm and mandibular thickness at the same level with a mean value of 10.7 mm to 12 mm. Line A' and Line A respectively of our study have also shown similar mean values.…”
Section: Discussionmentioning
confidence: 99%